Cuneiform Texts. Altbabylonische Rechts- und Wirtschaftsurkunden aus Tell ed-Dēr bei Sippar - Edzard, D. O. (1971)
Published by the Directorate General of Antiquities, Iraq; 253 Texte; Bearbeitung s. 32:375.